Production of Herbal Perfume from Peppermint, Kaffir Lime and Pandan - Md Kamaruddin, Nafisah @ Kamariah; Md Amin, Zulkarnain; A Aziz, Muhammad Shafiq Izham; Yusuf Hakim Khairuzzaan; Harol Hussein Salenga Herman (Multidisciplinary Applied Research and Innovation, 2021)
Perfumes and fragrances can be traced to multiple ancient cultures. For example, ancient Egypt used it to bathe daily, Greek medical thinker used as an ancient form of aromatherapy for health and vitality and Chinese used scent in the form of incense instead of perfumes to be worn. Leaves perfume have a lot of benefit for health. However, this perfume is not famous among younger generation as they do not know that leaves has greater quality of chemical compound than flowers. Therefore, in this research, pandan, mint and kaffir lime perfumes were produced and tested to younger generations. The perfumes were produced by using stem extract and leaf extract from the plant, and then by drying up the solution and lastly mixing with essential oil. A survey had been conducted at Universiti Tun Hussein Onn Malaysia with total of 90 respondents. The results of the questionnaire were analyzed using SPSS. For mint, from part A: Long Lasting, the mean is 3 with standard deviation 1, from part B: Benefit, the mean is 4 with standard deviation 1 and from part C: Smell, the mean is 4 with standard deviation 1. For kaffir lime, from part A: Long Lasting, the mean is 3 with standard deviation 1, from part B: Benefit, the mean is 4 with standard deviation 1 and from part C: Smell, the mean is 4 with standard deviation 1. For pandan, from part A: Long Lasting, the mean is 3 with standard deviation 0, from part B: Benefit, the mean is 3.4 with standard deviation 1 and from part C: Smell, the mean is 3.7 with standard deviation 1. In conclusion, students quite agree that plant perfume last longer while they agree that the perfumes smell nice and have benefits.